Synthesis, characterization and biological studies of S- benzyl-b-N-(benzoyl)dithiocarbazate and its metal complexes - How, Fiona Ni Foong; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim; Tarafder, Md. Tofassa Hossain; Cowley, Andrew R. (Elsevier, 2008)
S-Benzyl-b-N-(benzoyl) dithiocarbazate (SBNBODTC) a new disubstituted dithio-carbazate oxygen–sulfur (OS) donor ligand derived from reaction of S-benzyl dithiocarbazate with benzoyl chloride, formed bischelated complexes of general formula [M(OS)2] where M is Cu2+, Ni2+, Cd2+, Co2+ or Pb2+ and OS is a uninegative bidentate ligand. The ligand and its metal complexes have been characterized by a variety of physico-chemical techniques. S-benzyl-b-N-(benzoyl) dithiocarbazate crystallized with Z0 = 2 in its thione form in cis–cis conformation, with the N–N bond adopting a cis geometry with respect to C@S, while the S-benzyl group adopts a cis geometry with respect to the thione sulfur atom across the C–S bond.SBNBODTC, Cu(OS)2, Ni(OS)2 and Pb(OS)2 display marked cytotoxicity against HL-60 (human myeloid leukemia)while Cd(OS)2 and Co(OS)2 are moderately cytotoxic. The compounds showed moderate but selective activity towards targeted pathogens.